Counselling Services and Self-Esteem among Children with Physical Disabilities in Public Primary Schools in Anambra State - Chinwe Augustina Enwere; Queen Nneka Onunkwo (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
Children with physical disabilities in public primary schools often face unique psychological challenges, particularly regarding the development of their self-esteem. The study investigated the effects of counseling services on the growth of self-esteem in children with physical disabilities within public primary schools in Anambra State. Utilizing a descriptive survey research design, data were collected from a purposive sample of 100 respondents using a structured 4-point Likert questionnaire. Data analysis was conducted via SPSS, employing Pearson correlation, simple regression, and hierarchical multiple regression. A significant positive relationship was found between counseling services and self-esteem development, where r equals 0.506 and p equals 0.000. Regression analysis confirmed counseling services significantly predicted self-esteem, accounting for 25.6 percent of its development, with R squared at 0.256, F at 33.740, and p at 0.000. Demographic factors did not significantly moderate this relationship, as gender showed p at 0.359, age showed p at 0.549, and class level showed p at 0.675. Counseling services are crucial for increasing self-esteem among physically disabled children, independent of demographic factors. Consequently, schools should intensify counseling programs to enhance the mental health of these learners.